2019
DOI: 10.1016/j.taap.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic dynamics of human Sertoli cells are differentially modulated by physiological and pharmacological concentrations of GLP-1

Abstract: Obesity incidence has pandemic proportions and is expected to increase even further. Glucagon-like peptide-1 (GLP-1) based therapies are well-established pharmacological resources for obesity treatment. GLP-1 regulates energy and glucose homeostasis, which are also crucial for spermatogenesis. Herein, we studied the GLP-1 effects in human Sertoli cells (hSCs) metabolism and mitochondrial function. hSCs were cultured in absence or exposed to increasing doses of GLP-1 mimicking physiological post-prandial (0.01 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 50 publications
1
38
1
Order By: Relevance
“…Determination of mtDNA copy number. To study mtDNA copy number, we used a qPCR analysis in a CFX 96 thermocycler (Biorad, Hercules, CA), as described (40). Annealing temperatures and primer sequence are presented in Table 2.…”
Section: Chemicalsmentioning
confidence: 99%
“…Determination of mtDNA copy number. To study mtDNA copy number, we used a qPCR analysis in a CFX 96 thermocycler (Biorad, Hercules, CA), as described (40). Annealing temperatures and primer sequence are presented in Table 2.…”
Section: Chemicalsmentioning
confidence: 99%
“…Although the effects of GLP-1 in male reproduction remain overlooked, its contribution to glucose homeostasis suggests that it may be important for the regulation of spermatogenesis. The expression of the GLP-1 receptor was first identified in isolated human SCs by Martins et al ( 67 ). The authors also reported that exposure to GLP-1 decreased glucose consumption while increasing lactate production, in those cells.…”
Section: Multifactorial Effect Of Obesity In Sperm Qualitymentioning
confidence: 99%
“…The authors also reported that exposure to GLP-1 decreased glucose consumption while increasing lactate production, in those cells. Furthermore, GLP-1 modulates glucose metabolism of SCs and is suggested to have an anti-apoptotic effect in developing germ cells ( 67 ). In addition, it decreases T secretion ( 68 ), highlighting a possible effect in the hypothalamic–pituitary–gonadal (HPG) axis.…”
Section: Multifactorial Effect Of Obesity In Sperm Qualitymentioning
confidence: 99%
“…In fact, subfertility or infertility associated with metabolic diseases has been linked with SC metabolic dysregulation. A recent study reported that treatment of human SCs with glucagon-like peptide-1 (GLP-1) increased p-mTOR levels at Ser244 [124]. GLP-1 analogues are used for the treatment of diabetes and obesity [125] promoting weight loss.…”
Section: Mtor Pathway In Sertoli Cells and Male Fertilitymentioning
confidence: 99%